Medical Ward Round Teaching: A Mixed Methods Study to Explore the Perspective of Junior Doctors - Saima Bibi, Syed Yasir Hussain Gilani, Sobia Ali, Seemab Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the educational value of the ward round in medicine and allied wards for junior doctors and identify the barriers to effective learning during a round. Methodology: This mixed-method study was conducted over six months in the medicine and allied units of Ayub Teaching Hospital, Abbottabad. A semi-structured online questionnaire consisting of five and six point Likert-type scale responses was administered to 172 house officers and junior residents and data recorded through Google Forms. Data was analyzed by SPSS version 25.0 for descriptive statistics. The quantitative part was triangulated for validation with seven in-depth interviews from purposively selected participants which were thematically analyzed after assigning codes, categories and subthemes. Results: The response rate was 76.7%. The most important skill acquired during ward round was development of an approach towards patients 60(45.5%). This was followed by learning presentation skills 56(42.4%) and patient management 52(39.3%). Majority of the participants identified bed-side overcrowding 90(68.1%) to be the greatest barrier in learning during a round. Content analysis of the qualitative part suggested that an improvement in learning could be achieved by reducing the number of participants, introducing structured checklists and removing distractions for a consultant. Conclusion: Ward round is perceived to be an important tool for learning in medical education by junior doctors, but its full potential is not being utilized. Improvements can be made by changes made in the ward environment and structuring rounds by leading physicians.